Calibration and correction procedure for quantitative out-of-plane shearography. (20th February 2015) - Zastavnik, Filip; Pyl, Lincy; Gu, Jun; Sol, Hugo; Kersemans, Mathias; Van Paepegem, Wim
Abstract: Quantitative shearography applications continue to gain practical importance. However, a study of the errors inherent in shearography measurements, related to calibration of the instrument and correction of the results, is most often lacking. This paper proposes a calibration and correction procedure for the out-of-plane shearography with a Michelson interferometer. The calibration is based on the shearography measurement of known rigid-body rotations of a flat plate and accounts for the local variability of the shearing distance. The correction procedure further compensates for the variability of the sensitivity vector and separates the two out-of-plane deformation gradients when they are coupled in the measurement. The correction procedure utilizes two shearography measurements of the same experiment with distinct shearing distances. The effectiveness of the proposed calibration procedure is demonstrated in the case of a static deformation of a centrally loaded plate, where the discrepancy between experimental and finite element analysis results is minimized.